Customer relationships in the consolidated financial statements: Recognition and value relevance - Mingming Huang; Junsheng Zhang; Zheng Huo (China Journal of Accounting Studies (CJAS), 2022)
Customer relationships are important strategic resources. With a sample of A-share listed firms from 2007 to 2020 in China, this paper examines the recognition and value relevance of customer-related intangible assets. Current accounting standards require an acquirer to recognise identifiable intangible assets acquired in the business combination separately from goodwill. However, stakeholders question the usefulness of the information about customer relationships that are difficult to value reliably. The IASB and IFRIC have discussed a lot about whether to continue to separate customer-related intangible assets from goodwill. We find that firms with more R&D investments are more likely to recognise customer-related intangible assets. We also find that the book value of customer-related intangibles is positively associated with share price, which means recognised customer-related intangibles provide useful information to investors. We report empirical evidence in support of both international and Chinese accounting standards for separate recognition of identifiable intangible assets.
Keywords: 650; Customer relationships; value relevance; business combination; intangible assets